Perpustakaan Dalam Peradaban Islam - Wasto Wasto; Yuhdi Yuhdi; Budi Handrianto (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This paper discusses the library in Islamic civilization. Where the library is a window of knowledge and information because that is where the user will be able to discover new things. Libraries in Islamic history occupy an important position. Its existence is a crucial part of the development and progress of Islamic science and civilization. The main function of the library in the development of Islamic civilization is first, as a place of storage; second, as education; third, as research; fourth, as a means of information; and fifth as cultural recreation. Keywords: Library, Civilization, Islam